2004
DOI: 10.2134/jeq2004.1271
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Accumulation by the Halophyte Species Mediterranean Saltbush

Abstract: To identify Cd- and Zn-accumulating plants exhibiting a high growth rate, seeds from the halophyte species Mediterranean saltbush (Atriplex halimus L.) were collected on a heavy-metal-contaminated site in southeastern Spain (Llano del Beal, Cartagena). Seedlings from this ecotype were exposed for 3 wk to 0.1 mM Cd or Zn in a nutrient solution in a fully controlled environment. All plants remained alive and no significant growth inhibition was recorded until the end of the experiment. Mean Cd and Zn accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
3
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 41 publications
6
75
3
23
Order By: Relevance
“…A similar increase in root and leaf Zn as a response to 3-week exposure to 0.1 mM Cd in nutrient solution has been reported by Lutts et al (2004) with A. halimus. Moreover, Cd and Zn appear to compete for certain organic ligands in vivo.…”
Section: Treatmentssupporting
confidence: 83%
See 2 more Smart Citations
“…A similar increase in root and leaf Zn as a response to 3-week exposure to 0.1 mM Cd in nutrient solution has been reported by Lutts et al (2004) with A. halimus. Moreover, Cd and Zn appear to compete for certain organic ligands in vivo.…”
Section: Treatmentssupporting
confidence: 83%
“…Fodor et al (1996) demonstrated that in cucumber (Cucumis sativus L.), a strong inhibition of photosynthesis may result from Fe deficiency in Cd-treated plants. While 10 lM Cd reduced by more than 90 % the leaf Fe concentration of Cucumber, Lutts et al (2004) found that 0.1 mM Cd had no effect at all on the leaf Fe concentration of A. halimus.…”
Section: Treatmentsmentioning
confidence: 77%
See 1 more Smart Citation
“…The specific increase in Na + concentration observed in root and leaf tissues of plants simultaneously exposed to NaCl and Cu 2+ suggests that Na + could play a specific role in response to abiotic stress. Similarly, in other C4 species an increase in Na + endogenous content has been found after plant exposure to different abiotic stress conditions, this could be because Na is needed for an efficient phosphoenolpyruvate regeneration (Lutts et al, 2004). Cu 2+ and Cd 2+ induce the formation of harmful ROS, which causes irreversible damage to macromolecules such as lipid and proteins.…”
Section: Discussionmentioning
confidence: 91%
“…Experiments performed with A. halimus in pots of contaminated soil (Manousaki and Kalogerakis, 2009;Martí nezFernández and Walker, 2012;Pérez-Esteban et al, 2013), in hydroponic culture (Lefèvre et al, 2009;Lutts et al, 2004) or in Petri dishes (Márquez-Garcí a et al, 2013) show that its growth is tolerant of high concentrations of Cd, Cu, Mn, Ni, Pb or Zn in the medium. Lutts et al (2004) found that a 3-week exposure to elevated external Cd, whch produced leaf DM Cd concentrations as high as 618 μg g -1 , did not reduce shoot growth significantly, for plants of A. halimus grown from seeds of a population from a contaminated site in southern Spain. This indicates a very-high degree of tolerance, since values in excess of 5 μg g -1 are generally phytotoxic (Kabata-Pendias, 2001).…”
Section: Trace Elementsmentioning
confidence: 99%